2016
DOI: 10.1515/ngoe-2016-0003
|View full text |Cite
|
Sign up to set email alerts
|

The Examination of Factors Relating to the Leadership Style of Nursing Leaders in Hospitals

Abstract: Theories often describe leadership with different classifications, based on personality and behaviour, and have been used to establish the traits and behaviours that determine an effective leadership style. We used the quantitative methodology to investigate the determinants of the leadership style among nursing leaders in Slovene hospitals. Based on the results, we determined that demographic characteristics such as gender, age, length of employment, and level of education do not affect the choice of the lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
(11 reference statements)
1
7
0
Order By: Relevance
“…This present finding is supported by Alshahrani and Baig in pointing out that nurse leader employed transactional leadership as compared to transformational leadership [9]. Further, the findings of Lorber et al, demonstrated that most of the leaders used transactional leadership styles [12]. However, the study finding is contradicted with the study results of Abualrub and Alghamdi, and Moussa et al, who stated that Saudi nurses perceived their nurse leaders as transformational rather than transactional leaders [13,14].…”
Section: Discussionsupporting
confidence: 56%
“…This present finding is supported by Alshahrani and Baig in pointing out that nurse leader employed transactional leadership as compared to transformational leadership [9]. Further, the findings of Lorber et al, demonstrated that most of the leaders used transactional leadership styles [12]. However, the study finding is contradicted with the study results of Abualrub and Alghamdi, and Moussa et al, who stated that Saudi nurses perceived their nurse leaders as transformational rather than transactional leaders [13,14].…”
Section: Discussionsupporting
confidence: 56%
“…Democratic leadership style helps to boost morale the morale of employess because employees make contributions to the decision making process. It makes subordinates to feel that their opinions matter in the management of the organization (Lorber & Treven, 2016). Adeyemi (2010) orates that in democratic style of leadership, emphasis is placed on group and leader participation in the making of policies.…”
Section: Democratic Leadership Style and Teacher Motivationmentioning
confidence: 99%
“…It is perhaps no coincidence therefore that within the health service around the world, transactional styles of leadership are by far the most common (Lorber, Treven, and Mumel 2016). However, despite the high rates of prevalence of transactional leadership within such settings, there is a view that such leadership styles are not as effective for the development of team morale and engagement (Lorber et al 2016). This exposes the tension that can often occur between the attainment of organisational goals and the cultivation of a nurturing environment for individual team members (Hamstra et al 2014).…”
Section: Transactional Leadershipmentioning
confidence: 99%
“…In the context of student leadership, transformational leadership has been identified as a challenging theoretical foundation for the development of formal student leadership due to its styles that are not as effective for the development of team morale and engagement as stated by Lorber et al (2016). However, this leadership theory is widely used in educational institutions in the relationship between instructors and students.…”
Section: Transactional Leadershipmentioning
confidence: 99%